UNUSUAL FOREIGN BODIES IN THE RESPIRATORY TRACT IN CHILDREN - D. M. Mustafayev; V. M. Svistushkin (Неотложная медицинская помощь)
The authors report 4 clinical cases from own practice of unusual foreign bodies in the lower respiratory tract in children. The diagnosing procedure and aspects of surgical treatment have been analyzed. The modern endoscopic equipment was used to remove foreign bodies.